The PEA-15 protein regulates autophagy via activation of JNK - Böck, Barbara; Tagscherer, Katrin; Faßl, Anne; Krämer, Anika; Oehme, Ina; Zentgraf, Hanswalter; Keith, Martina; Roth, Wilfried (The journal of biological chemistry, 2010)
PEA-15/PED (phosphoprotein enriched in astrocytes 15 kDa/phosphoprotein enriched in diabetes) is a death effector domain-containing protein which is known to modulate apoptotic cell death. The mechanism by which PEA-15 inhibits caspase activation and increases ERK (extracellular-regulated kinase) activity is well characterized. Here, we demonstrate that PEA-15 is not only pivotal in the activation of the ERK pathway but also modulates JNK (c-Jun N-terminal kinase) signaling. Upon overexpression of PEA-15 in malignant glioma cells, JNK is potently activated. The PEA-15-induced JNK activation depends on the phosphorylation of PEA-15 at both phosphorylation sites (serine 104 and serine 116). The activation of JNK is substantially inhibited by siRNA-mediated down-regulation of endogenous PEA-15. Moreover, we demonstrate that glioma cells overexpressing PEA-15 show increased signs of autophagy in response to classical autophagic stimuli such as ionizing irradiation, serum deprivation, or rapamycin treatment. In contrast, the non-phosphorylatable mutants of PEA-15 are not capable of promoting autophagy. The inhibition of JNK abrogates the PEA-15-mediated increase in autophagy. In conclusion, our data show that PEA-15 promotes autophagy in glioma cells in a JNK-dependent manner. This might render glioma cells more resistant to adverse stimuli such as starvation or ionizing irradiation.